What Should Be Considered in Bethesda III Thyroid Nodules When Prefering Hemitioidectomy or Total Thyroidectomy - Fazilet Altın; Mürüvvet Paksoy (Haseki Tıp Bülteni, 2020)

(untitled)
Aim:The aim of study was to retrospectively examine the files of patients operated on for Bethesda category III thyroid nodules, to evaluate the criteria that were taken into consideration for surgical decisions, and predictive factors for malignancy.Methods:Patients, who underwent surgery for Bethesda category III thyroid nodules based on preoperative fine-needle aspiration biopsy (FNAB) results between 2014 and 2019 in our clinic, were analyzed retrospectively.Results:Of the 90 patients included in the study, 18 (20%) were male and 72 (80%) were female, and the mean age was 48.39±12.96 years (18-84). The mean nodule diameter was 23.67±11.49 mm (6-55). The results of FNAB were atypia of undetermined significance in 80 (88.89%) and follicular lesion of undetermined significance in 10 (11.11%) patients. The most common benign postoperative pathology was nodular hyperplasia in 26 (42.22%) and the most common malignant pathology was papillary thyroid carcinoma in 33 (36.67%) patients. Complementary thyroidectomy was performed in 19 (26.02%) of 26 (35.61%) patients after lobeistmectomy and seven (9.59%) were followed up. In the logistic regression analysis of determinants/risk factors for malignancy, microcalcification and edge irregularity were found to be the most significant factors (p=0.009, p0.001 and p0.001, respectively).Conclusion:The Bethesda classification used in thyroid nodules continues to pose a dilemma for many surgeons. In patients with Bethesda III nodules, family history, ultrasonography findings (microcalcification, edge irregularity, the nature and number of nodules in the other lobe), and patient and surgeon preference should be taken into consideration when making a decision for surgery.